Magnetization process in the exactly solved spin-1/2 Ising-Heisenberg model on decorated Bethe lattices - Strečka, J.; Ekiz, C. (Condensed Matter Physics, 2012)
The spin-1/2 Ising-Heisenberg model on diamond-like decorated Bethe lattices is exactly solved in the presence of the longitudinal magnetic field by combining the decoration-iteration mapping transformation with the method of exact recursion relations. In particular, the ground state and low-temperature magnetization process of the ferrimagnetic version of the considered model is investigated in detail. Three different magnetization scenarios with up to two consecutive fractional magnetization plateaus were found, whereas the intermediate magnetization plateau may either correspond to the classical ferrimagnetic spin arrangement and/or the field-induced quantum ferrimagnetic spin ordering without any classical counterpart. Спiн-1/2 модель Iзинга-Гайзенберга на ромбоподiбнiй декорованiй гратцi Бете розв’язано точно у присутностi поздовжнього магнiтного поля, поєднуючи декорацiйно-iтерацiйне перетворення з методом точних рекурсивних спiввiдношень. Зокрема, детально дослiджено основний стан i низькотемпературне намагнiчення феримагнiтної версiї розглянутої моделi. Знайдено три рiзнi сценарiї намагнiченостi з що-найбiльше двома послiдовними дробовими плато, де промiжне плато намагнiченостi може вiдповiдати класичному феримагнiтному спiновому впорядкуванню та/або iндукованому полем квантовому феримагнiтному спiновому впорядкуванню, яке не має жодного класичного аналога.